Oncologic Safety of Immediate Breast Reconstruction: A Single-Center Retrospective Review of 138 Patients. Issue 6 (December 2021) - Hammer, Jennifer; Servaes, Maxime; Berners, Aline; Deconinck, Christine; Pirson, Geneviève; Fosseprez, Philippe
Abstract : Objective: The purpose of this study was to assess the oncologic safety of mastectomies associated with immediate breast reconstruction (IBR) in terms of recurrence and survival. Methods: A retrospective review was conducted at a single center (CHU UCL Namur, Belgium). We analyzed the oncologic safety of IBR for patients with invasive and in situ breast cancer who underwent mastectomy associated with IBR. Patients who underwent palliative surgery and those with a diagnosis of breast sarcoma were excluded. Results: We retrospectively analyzed 138 patients who underwent mastectomy and IBR between January 2012 and December 2019. Most reconstruction procedures used deep inferior epigastric perforator free flaps (55.1%). The reconstructive failure rate was 8.7%. Among the patients included, 5 cases of local cancer recurrence, 1 case of local cancer recurrence associated with distant metastasis, and 2 cases of systemic recurrence were identified during a mean follow-up of 49.3 months (range, 8–104 months) after surgery. Overall survival was 97.8%, and disease-free survival was 94.2%. Conclusions: Patients had a low incidence of cancer recurrence in this review. Immediate breast reconstruction after mastectomy had no negative impact on recurrence or patient survival, even in patients with advanced disease. The study findings suggest that mastectomy associated with IBR can be a safe surgical option for patients with invasive and noninvasive breast cancers. Longer follow-ups are needed to confirm these preliminary results.